PERBANDINGAN PENYELESAIAN PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA DI INDONESIA DAN KOREA SELATAN: Comparative Study of Employment Termination Dispute Resolution in Indonesia and South Korea - Ballah, Altiara Nazma Aulia; Alfianto, Dwi (Faculty of Law, Universitas Trisakti, 2025)
The relationship between workers and employers doesn’t always go well, many problems arise such as disputes over rights, and interests, termination of employment, and disputes between trade unions/labor unions in one company. Disputes in industrial relations cannot be avoided because we must have different opinions as humans. Termination of employment dispute is the most common dispute in Indonesia compared to the other three industrial relations disputes. Termination of employment disputes occurs not only in Indonesia but also in South Korea. The problem in this study is to compare the regulations for resolving employment termination disputes In both Countries. This research uses normative research type, namely legal comparison, and descriptive which requires secondary data. Data for this research will be collected using a literature study with qualitative analysis and a deductive method. The results obtained in this study show the differences and similarities of regulations in resolving employment termination disputes where the process of resolving layoff disputes in South Korea and Indonesia both prioritize negotiations, and the difference is that in South Korea the Labor Relations Commission (LRC) institution is known to get to the court stage, which must pass an examination through the regional LRC after the National LRC then goes to the administrative court.